Cost-effectiveness of pre-exercise carbohydrate meals and their impact on endurance performance - Paddon-Jones, D. J.; Pearson, D. R. (The Journal of Strength and Conditioning Research, 1998)
This study examined the effects of ingesting 4 isocaloric carbohydrate (CHO) meals 2 hrs prior to a 60-min bout of endurance cycling. Each meal represented a different combination of type, form, or mode of delivery of CHO: (a) semi-liquid, oat based CHO/fat/protein combination (Combo); (b) semi-liquid, oat based CHO (Oat); (c) semi-liquid, wheat based CHO (Wheat); (d) dense solid, fructose based CHO/protein/vitamin combination (Bar). Cost of the meals ranged from $0.50 to $2.60 each. Trials were conducted in random order over a 4-week period. Exercise and diet was standardized prior to each trial. Feedings were ingested 2 hrs before each 60-min self-paced cycle ergometry trial. Dependent variables were assessed every 15 min during each trial. Regardless of which meal was ingested, no significant group differences were found for blood glucose concentration, distance traveled, heart rate, oxygen consumption, or respiratory exchange ratio. It is suggested that some endurance athletes may save money yet suffer no performance disadvantage with CHO-based cereal instead of the more costly commercial sports bars.